1980
DOI: 10.1115/1.3230368
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Loss in a Gas Turbine Stage with Film Cooling

Abstract: Experiments have been performed to measure the total pressure loss of the flow through a two-dimensional turbine cascade with “coolant” injection from a single row of holes on the suction or pressure side of the blades. The tests were performed in a low speed tunnel. Air and carbon dioxide were used as secondary fluids, the latter to provide a large density difference between the gas in the mainstream and the injected gas. Both gas streams had the same temperature. The measured pressure loss is in good agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…This is caused by the superposition of two effects: one is the well-known fact, e.g. Ito et al (1980) and Arts (1992), that the presence of the holes may both trigger the transition of the boundary layer and increase the turbulence of a turbulent boundary layer; the other is due to the fraction of the mainstream entering the hollow cavity in the leading edge region and exiting from the suction side and from the trailing edge holes, thus experiencing an additional dissipation. In order to separate these two effects the holes should be sealed from the inside; however, this was not done in the course of the present work.…”
Section: Film Cooling Test Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is caused by the superposition of two effects: one is the well-known fact, e.g. Ito et al (1980) and Arts (1992), that the presence of the holes may both trigger the transition of the boundary layer and increase the turbulence of a turbulent boundary layer; the other is due to the fraction of the mainstream entering the hollow cavity in the leading edge region and exiting from the suction side and from the trailing edge holes, thus experiencing an additional dissipation. In order to separate these two effects the holes should be sealed from the inside; however, this was not done in the course of the present work.…”
Section: Film Cooling Test Conditionsmentioning
confidence: 99%
“…Several previously published papers investigated this problem on the base of cascade testing; most of them examined the effects of individual injection rows, depending on their position along the blade surface. Ito et al(1980) reported on the influence of early injection on suction and pressure side at low speed. Kost and Holmes (1985) investigated different trailing edge injection configurations for a transonic rotor blade; they separated the injection loss from the profile loss as a function of coolant flow rate, by considering the base pressure changes.…”
Section: Introductionmentioning
confidence: 99%
“…Willett and Fottner (1994) performed an experiment about the mixing process at turbine blades, especially on the suction side. Ito et al (1980) measured the local pressure losses in a cascade with air ejection in order to simulate the film cooling. They also predicted the mixing pressure loss analytically by assuming a mixing at constant static pressure and made a comparison between experiment and prediction.…”
Section: Nomenclature Amentioning
confidence: 99%
“…However, the simulated mass flow and efficiency underline the need for a cooling loss model. Subsequent development efforts will tend to introduce an one-dimensional mixing model for the evaluation of the cooling losses [39,40].…”
Section: Discussionmentioning
confidence: 99%